Adhesives, laminates, packaging materials
A two-component curing adhesive, comprising a polyol composition and a polyisocyanate composition, effectively addresses the issue of delamination in packaging materials under high-temperature conditions, enhancing the durability and safety of packaged goods.
Patent Information
- Application Number
- JP2024536477
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2042-12-29
AI Technical Summary
Packaging materials used for food and other products often experience delamination when subjected to high-temperature and high-humidity conditions, such as boiling, due to the failure of adhesives to maintain bonding under these stressors.
A two-component curing adhesive is developed, comprising a polyol composition containing a reaction product of polyvalent carboxylic acid, polyhydric alcohol, and a compound with an alkoxysilyl group, combined with a polyisocyanate composition. This adhesive forms a strong bond between substrates, enhancing resistance to delamination under high-temperature conditions.
The adhesive significantly reduces the likelihood of delamination in packaging materials even when exposed to boiling treatments, ensuring the integrity and safety of packaged contents.
Smart Images

Figure 0007655448000001 
Figure 0007655448000002 
Figure 0007655448000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive, a laminate obtained by using the adhesive, and a packaging material. [Background technology]
[0002] Multilayer laminates of metal foils such as aluminum foil or metal-deposited films and plastic films such as polyethylene, polypropylene, vinyl chloride, polyester, and nylon are used as packaging materials for foods, medical products, cosmetics, daily necessities, etc. These laminates are made by appropriately combining various plastic films, metal-deposited films, or metal foils and laminating them with various adhesives according to the required characteristics of each application (Patent Documents 1 to 4). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2000-263682 A [Patent Document 2] JP 2000-177771 A [Patent Document 3] JP 2000-154365 A [Patent Document 4] Japanese Patent Application Publication No. 9-295386 Summary of the Invention [Problem to be solved by the invention]
[0004] Some packaging materials are filled with food, beverages, or other contents and then subjected to a heat treatment under high temperature and humidity conditions, such as boiling. During this process, delamination may occur between the adhesive and the film or metal vapor deposition layer.
[0005] The present invention has been made in consideration of the above circumstances, and aims to provide a two-component curing adhesive that is less likely to cause delamination even when subjected to high-temperature heat treatment such as boiling, and a laminate and packaging material obtained using the adhesive. [Means for solving the problem]
[0006] The present invention relates to a two-component curing adhesive comprising: a polyol composition (X) containing a reaction product (A) of a composition (A') containing a polyvalent carboxylic acid (a), a polyhydric alcohol (b), and a compound (c) having a functional group reactive with a carboxyl group or a hydroxyl group, and an alkoxysilyl group; and a polyisocyanate composition (Y).
[0007] The present invention further relates to a laminate including a first substrate, a second substrate, and an adhesive layer bonding the first substrate and the second substrate, the adhesive layer being a cured coating film of the above-mentioned two-component curing adhesive, and a packaging material comprising the laminate. Effect of the Invention
[0008] The adhesive of the present invention can provide laminates and packaging materials that are less susceptible to delamination even when subjected to high-temperature heat treatment such as boiling. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] <Adhesive> The adhesive of the present invention is a two-component curing adhesive comprising a polyol composition (X) and a polyisocyanate composition (Y). The adhesive of the present invention will be described in detail below.
[0010] (Polyol composition (X)) (Reaction Product (A)) The polyol composition (X) used in the adhesive of the present invention comprises a reaction product (A) of a composition (A') which comprises a polyvalent carboxylic acid (a), a polyhydric alcohol (b), and a compound (c) having a functional group reactive with a carboxyl group or a hydroxyl group, and an alkoxysilyl group.
[0011] The polycarboxylic acid (a) may be a known compound that has been conventionally used in the synthesis of polyester polyols. Specific examples of the polycarboxylic acid (a) include aliphatic polycarboxylic acids such as malonic acid, ethylmalonic acid, dimethylmalonic acid, succinic acid, 2,2-dimethylsuccinic acid, succinic anhydride, alkenyl succinic anhydride, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, fumaric acid, maleic acid, maleic anhydride, itaconic acid, dimer acid, and trimer acid;
[0012] Alkyl esters of aliphatic polycarboxylic acids, such as dimethyl malonate, diethyl malonate, dimethyl succinate, dimethyl glutarate, dimethyl adipate, diethyl pimelate, diethyl sebacate, dimethyl fumarate, diethyl fumarate, dimethyl maleate, and diethyl maleate;
[0013] alicyclic polycarboxylic acids such as 1,1-cyclopentanedicarboxylic acid, 1,2-cyclopentanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, tetrahydrophthalic anhydride, 4-methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, cyclohexane-1,2,4-tricarboxylic acid-1,2-anhydride, himic anhydride, and HET anhydride;
[0014] Aromatic polycarboxylic acids such as orthophthalic acid, terephthalic acid, isophthalic acid, phthalic anhydride, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic anhydride, naphthalic acid, trimellitic acid, trimellitic anhydride, pyromellitic acid, pyromellitic anhydride, biphenyldicarboxylic acid, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid, benzophenonetetracarboxylic acid, benzophenonetetracarboxylic dianhydride, 5-sodium sulfoisophthalic acid, tetrachlorophthalic anhydride, and tetrabromophthalic anhydride;
[0015] methyl esters of aromatic polycarboxylic acids such as dimethyl terephthalic acid and dimethyl 2,6-naphthalenedicarboxylate; and the like. These may be used alone or in combination of two or more.
[0016] The polyhydric alcohol (b) is not particularly limited, and bifunctional or trifunctional or higher alcohols can be used. Examples of bifunctional alcohols include aliphatic diols such as ethylene glycol, diethylene glycol, propylene glycol, 1,3-propanediol, 1,2,2-trimethyl-1,3-propanediol, 2,2-dimethyl-3-isopropyl-1,3-propanediol, 1,4-butanediol, 1,3-butanediol, 3-methyl-1,3-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,4-bis(hydroxymethyl)cyclohexane, 2,2,4-trimethyl-1,3-pentanediol, and dimer diol; Ether glycols such as polyoxyethylene glycol and polyoxypropylene glycol; Modified polyether diols obtained by ring-opening polymerization of aliphatic diols with various cyclic ether bond-containing compounds such as ethylene oxide, propylene oxide, tetrahydrofuran, ethyl glycidyl ether, propyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, and allyl glycidyl ether; Lactone-based polyester polyols obtained by polycondensation reaction of aliphatic diols with various lactones such as lactonoids and ε-caprolactone; Bisphenols such as bisphenol A and bisphenol F; Examples of the alkylene oxide adducts include those obtained by adding ethylene oxide, propylene oxide, or the like to bisphenols such as bisphenol A and bisphenol F.
[0017] The tri- or higher functional polyols include aliphatic polyols such as trimethylolethane, trimethylolpropane, glycerin, hexanetriol, and pentaerythritol; Modified polyether polyols obtained by ring-opening polymerization of aliphatic polyols with various cyclic ether bond-containing compounds such as ethylene oxide, propylene oxide, tetrahydrofuran, ethyl glycidyl ether, propyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, and allyl glycidyl ether; Examples of the polyol include lactone-based polyester polyols obtained by polycondensation reaction of an aliphatic polyol with various lactones such as ε-caprolactone.
[0018] Examples of the functional group possessed by the compound (c) having a functional group reactive with a carboxyl group or a hydroxyl group and an alkoxysilyl group include an epoxy group, an amino group, an isocyanate group, etc. In the following, for the sake of simplicity, the functional group possessed by the compound (c) having a reactive group with a carboxyl group or a hydroxyl group is also simply referred to as the functional group (c').
[0019] Specific examples of the compound (c) include compounds (c1) having amino and alkoxysilyl groups, such as N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, and N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane;
[0020] Compounds (c2) having an epoxy group and an alkoxysilyl group, such as 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 3-glycidoxypropyltriethoxysilane;
[0021] Examples of the compound (c3) include a compound having an isocyanate group and an alkoxysilyl group, such as 3-isocyanatepropyltriethoxysilane and tris-(trimethoxysilylpropyl)isocyanurate.
[0022] The polyvalent carboxylic acid (a) and the polyhydric alcohol (b) in the composition (A') are mixed so that the number of moles of hydroxyl groups in the polyhydric alcohol (b) is in excess relative to the number of moles of carboxyl groups in the polyvalent carboxylic acid (a).
[0023] The amount of compound (c) in composition (A') can be adjusted as appropriate, but from the viewpoint of more reliably expressing boiling resistance, it is preferable that it is 0.05 mass% or more of composition (A'). If the amount of compound (c) is too large, the viscosity of reaction product (A) increases, and it may be difficult to remove from the production equipment. From the viewpoint of production efficiency, it is preferable that the amount of compound (c) in composition (A') is 10 mass% or less.
[0024] The hydroxyl value of the reaction product (A) is appropriately adjusted depending on the purpose, and is, for example, 1 mgKOH / g. The hydroxyl value and acid value of the reaction product can be measured by the method described in JIS-K0070.
[0025] The reaction product (A) is obtained, for example, by polycondensing (esterifying) the composition (A') by a known, conventional method. Specifically, the composition (A') is charged into a reaction vessel equipped with a stirrer and a rectification device, and heated to about 130°C under normal pressure to 0.5 MPa while stirring. Thereafter, the temperature is raised at a reaction temperature of 130 to 260°C at a rate of 5 to 10°C / hour to distill off the water and other products produced. After the polycondensation reaction is carried out for 4 to 12 hours, the degree of pressure reduction is gradually increased from normal pressure to 1 to 300 torr, and the excess polyhydric alcohol (b) and other products are distilled off to promote the reaction.
[0026] For composition (A'), the temperature may be increased when the polyvalent carboxylic acid (a), the polyhydric alcohol (b), and the compound (c) are all placed in a reaction vessel, or the temperature may be increased when only the polyhydric alcohol (b) is placed in a reaction vessel, and when a certain temperature is reached, the polyvalent carboxylic acid (a) and the compound (c) are added to initiate the reaction.
[0027] A catalyst may be used in combination during polycondensation. The polymerization catalyst is preferably at least one metal selected from the group consisting of Groups 2, 4, 12, 13, 14, and 15 of the periodic table, or a compound of the metal. Examples of the polymerization catalyst made of such a metal or a compound of the metal include metals such as Ti, Sn, Zn, Al, Zr, Mg, Hf, and Ge, and compounds of these metals, more specifically titanium tetraisopropoxide, titanium tetrabutoxide, titanium oxyacetylacetonate, tin octanoate, 2-ethylhexanetin, zinc acetylacetonate, zirconium tetrachloride, zirconium tetrachloride tetrahydrofuran complex, hafnium tetrachloride, hafnium tetrachloride tetrahydrofuran complex, germanium oxide, and tetraethoxygermanium.
[0028] Preferred examples of commercially available polymerization catalysts include Orgatix TA series, TC series, ZA series, ZC series, and AL series manufactured by Matsumoto Fine Chemical Co., Ltd., and organotin catalysts, inorganic metal catalysts, and inorganic tin compounds manufactured by Nitto Kasei Co., Ltd.
[0029] The amount of the polymerization catalyst used is not particularly limited as long as the reaction can be controlled, but is, for example, 10 to 1000 ppm, preferably 20 to 800 ppm, based on the total amount of the composition (A'). In order to suppress coloration of the reaction product (A), it is more preferably 30 to 500 ppm.
[0030] The reaction product (A) may be obtained by further carrying out a urethane reaction after the above-mentioned polycondensation reaction. The urethane reaction proceeds by heating the polycondensate of the composition (A') and the isocyanate compound (d) at 60 to 100°C in the presence of a chain extension catalyst and a solvent, which are used as necessary.
[0031] The isocyanate compound (d) used in the urethanization reaction is not particularly limited, and examples thereof include aromatic diisocyanates, araliphatic diisocyanates, aliphatic diisocyanates, alicyclic diisocyanates, and biuret, nurate, adduct, allophanate, carbodiimide-modified, and uretdione-modified products of these diisocyanates, and these can be used alone or in combination.
[0032] Examples of aromatic diisocyanates include, but are not limited to, 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate (also called polymeric MDI or crude MDI), 1,3-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,4-phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-toluidine diisocyanate, 2,4,6-triisocyanate toluene, 1,3,5-triisocyanate benzene, dianisidine diisocyanate, 4,4'-diphenyl ether diisocyanate, and 4,4',4"-triphenylmethane triisocyanate.
[0033] The araliphatic diisocyanate means an aliphatic isocyanate having one or more aromatic rings in the molecule, and examples thereof include, but are not limited to, m- or p-xylylene diisocyanate (also known as XDI), α,α,α',α'-tetramethylxylylene diisocyanate (also known as TMXDI), and the like.
[0034] Examples of aliphatic diisocyanates include, but are not limited to, trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (also known as HDI), pentamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.
[0035] Examples of alicyclic diisocyanates include, but are not limited to, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate, isophorone diisocyanate (also known as IPDI), 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), and 1,4-bis(isocyanatomethyl)cyclohexane.
[0036] The low molecular weight polyol used in the synthesis of these isocyanate adducts may be any of those known in the art, such as trimethylolpropane.
[0037] The chain extension catalyst may be a known catalyst used as a normal urethane catalyst, and may be an organic tin compound, an organic tin carboxylate, a lead carboxylate, a bismuth carboxylate, a titanium compound, a zirconium compound, or the like. The amount of the chain extension catalyst used may be an amount that sufficiently promotes the reaction between the polycondensate of the composition (A') and the isocyanate compound (d), and as an example, the amount is preferably 5.0% by mass or less based on the total amount of the polycondensate of the composition (A') and the isocyanate compound (d). In order to suppress hydrolysis or coloration of the resin caused by the catalyst, the amount is more preferably 1.0% by mass or less.
[0038] Examples of good solvents that can be used in the urethanization reaction include methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl ethyl ketone, methyl isobutyl ketone, propylene glycol monomethyl ether acetate, toluene, xylene, etc. They may be used alone or in combination of two or more.
[0039] The urethane reaction is carried out until the isocyanate groups derived from the isocyanate compound (d) used in the reaction are substantially all consumed. The remaining amount of isocyanate groups can be confirmed by infrared absorption spectroscopy, for example, by measuring the absorption spectrum derived from the isocyanate groups at 2260 cm -1 Examples of methods for determining the amount of isocyanate groups include checking for the presence or absence of an absorption peak observed in the vicinity of the isocyanate group, and quantifying the amount of isocyanate groups by titration.
[0040] In the polymerization reaction of the composition (A'), in addition to the polyester polyol (A1) produced by the esterification reaction of the polycarboxylic acid (a) and the polyhydric alcohol (b), various by-products may be produced, such as compound (A2) in which at least one of the polycarboxylic acid (a), the polyhydric alcohol (b), and the polyester polyol (A1) is bonded to the compound (c) via a functional group (c'), compound (A3) in which the alkoxysilyl group of the compound (c) is hydrolyzed to become a silanol group by the reaction of the water generated during the esterification reaction with the compound (c), and polycondensate (A4) of the compound (A3). That is, the reaction product (A) is a mixture of these. Surprisingly, it has been revealed by the present invention that these by-products contribute to the boiling resistance of the adhesive.
[0041] As a means for improving boil resistance, a method of adding a silane coupling agent is widely known. However, in this method, when the silane coupling agent is added to the polyol composition (X) and / or the polyisocyanate composition (Y) or when the adhesive is cured, the alkoxysilyl group of the silane coupling agent reacts with water or isocyanate present in the system, and alcohol derived from the alkoxysilyl group is generated and remains in the cured coating film of the adhesive, which may cause the alcohol to migrate to the contents. In particular, when a silane coupling agent having a methoxy group is used, methanol remains, so it is not preferable as an adhesive used for manufacturing food packaging materials. In contrast, the present invention can provide an adhesive in which such concerns are suppressed because the alcohol derived from the alkoxysilyl group of the compound (c) volatilizes during polycondensation of the composition (A').
[0042] (Polyol (B)) The polyol composition (X) may contain a polyol (B) other than the reaction product (A). Examples of such polyol (B) include polyester polyol, polyester polyether polyol, polyester polyurethane polyol, polyether polyol, polyether polyurethane polyol, polyurethane polyol, vegetable oil polyol, polycarbonate polyol, etc. The same polyhydric alcohol (b) exemplified as the raw material of the reaction product (A) can be used.
[0043] As the polyvalent carboxylic acid and polyhydric alcohol used in the synthesis of the polyol having a polyester skeleton, the same ones as those exemplified for the polyvalent carboxylic acid (a) and polyhydric alcohol (b) can be used. As the isocyanate compound used in the synthesis of the polyol having a polyurethane skeleton, the same compounds as those exemplified as the isocyanate compound (d) can be used.
[0044] Examples of polyether polyols include those obtained by ring-opening polymerization of polyoxyethylene glycol, polyoxypropylene glycol, and aliphatic polyols with various cyclic ether bond-containing compounds such as ethylene oxide, propylene oxide, tetrahydrofuran, ethyl glycidyl ether, propyl glycidyl ether, butyl glycidyl ether, phenyl glycidyl ether, and allyl glycidyl ether. Examples of the oil include castor oil, dehydrated castor oil, hydrogenated castor oil which is a hydrogenated product of castor oil, and an adduct of 5 to 50 moles of alkylene oxide with castor oil.
[0045] The hydroxyl value of the polyester polyol (B) is appropriately adjusted depending on the purpose, and is, for example, 1 mgKOH / g. The hydroxyl value and acid value of the reaction product can be measured by the method described in JIS-K0070.
[0046] The amount of polyol (B) may be adjusted as appropriate, but as an example, the proportion of the reaction product (A) in the total amount of the reaction product (A) and the polyol (B) is 10 mass% or more, which can more reliably provide an adhesive with excellent boiling resistance.
[0047] When the adhesive of the present invention is used in the form of a solventless adhesive described later, the viscosity of the polyol composition (X) is adjusted to a range suitable for the non-solvent lamination method. For example, the viscosity at 40 to 60°C is adjusted to be in the range of 100 to 5000 mPas, more preferably 500 to 3000 mPas. The viscosity of the polyol composition (X) can be adjusted, for example, by the skeleton and number average molecular weight of the reaction product (A) and polyol (B), and the plasticizer (D4) described later.
[0048] (Polyisocyanate composition (Y)) The polyisocyanate composition (Y) contains a polyisocyanate compound (C) having a plurality of isocyanate groups. The polyisocyanate compound (C) is not particularly limited, and examples thereof include aromatic diisocyanates, araliphatic diisocyanates, aliphatic diisocyanates, alicyclic diisocyanates, and biuret, nurate, adduct, allophanate, carbodiimide-modified, and uretdione-modified products of these diisocyanates, and urethane prepolymers obtained by reacting these polyisocyanates with polyols, and these can be used alone or in combination.
[0049] As the aromatic diisocyanate, araliphatic diisocyanate, aliphatic diisocyanate, and alicyclic diisocyanate, the same compounds as those exemplified as the isocyanate compound (d) can be used.
[0050] Examples of polyols used in the synthesis of the urethane prepolymer include those exemplified as polyol (B). When a urethane prepolymer is used as the polyisocyanate compound (C), it is preferable to use at least one of polyalkylene glycol and polyester polyol, since this can reduce the viscosity of the adhesive and increase the adhesive strength.
[0051] For flexible packaging substrates, polyisocyanates obtained by reacting aromatic polyisocyanates with polyalkylene glycols having a number average molecular weight in the range of 200 to 6,000, and polyisocyanates obtained by reacting aromatic polyisocyanates with polyester polyols having a number average molecular weight in the range of 200 to 3,000 are preferred because they can impart appropriate flexibility to the cured product. Polyisocyanates with an isocyanate content of 5 to 20% by mass as determined by titration method (using di-n-butylamine) are preferred because they provide appropriate resin viscosity and excellent coatability.
[0052] For hard substrates, polyisocyanates obtained by reacting aromatic polyisocyanates with polyester polyols having a number average molecular weight in the range of 200 to 3,000, and polyisocyanates obtained by reacting aromatic polyisocyanates with a mixture of polyester polyols having a number average molecular weight in the range of 200 to 3,000 and polyalkylene glycols having a number average molecular weight in the range of 200 to 6,000 are preferred from the viewpoint of excellent adhesive strength. Polyisocyanates having an isocyanate content of 5 to 20 mass% according to a standard method (using di-n-butylamine) are also preferred from the viewpoint of appropriate resin viscosity and excellent coatability.
[0053] When the polyisocyanate compound (C) is a urethane prepolymer, the equivalent ratio [NCO] / [OH] of the isocyanate group and the hydroxyl group subjected to the synthesis reaction is preferably in the range of 1.5 to 5.0, since this brings the viscosity of the adhesive into an appropriate range and improves the coatability.
[0054] When the adhesive of the present invention is used in the form of a solventless adhesive described later, the viscosity of the polyisocyanate composition (Y) is adjusted to a range suitable for the non-solvent lamination method. For example, the viscosity at 40°C is adjusted to be in the range of 500 to 5000 mPas, more preferably 500 to 3000 mPas. The viscosity of the polyisocyanate composition (Y) can be adjusted, for example, by the amount of the urethane prepolymer or the amount of the low molecular weight isocyanate compound.
[0055] (Other components of adhesive (D)) The adhesive of the present invention may contain other components than those mentioned above. The other component (D) may be contained in either or both of the polyol composition (X) and the polyisocyanate composition (Y), or may be prepared separately from these and mixed with the polyol composition (X) and the polyisocyanate composition (Y) immediately before application of the adhesive. Each component will be described below.
[0056] (Catalyst (D1)) Examples of the catalyst (D1) include metal catalysts, amine catalysts, and aliphatic cyclic amide compounds.
[0057] Examples of the metal catalyst include metal complex catalysts, inorganic metal catalysts, and organic metal catalysts. Examples of the metal complex catalyst include acetylacetonate salts of metals selected from the group consisting of Fe (iron), Mn (manganese), Cu (copper), Zr (zirconium), Th (thorium), Ti (titanium), Al (aluminum), and Co (cobalt), such as iron acetylacetonate, manganese acetylacetonate, copper acetylacetonate, and zirconia acetylacetonate.
[0058] Examples of inorganic metal catalysts include those selected from Sn, Fe, Mn, Cu, Zr, Th, Ti, Al, Co, etc.
[0059] Examples of the organometallic catalyst include organozinc compounds such as zinc octylate, zinc neodecanoate, and zinc naphthenate; organotin compounds such as stannous diacetate, stannous dioctoate, stannous dioleate, stannous dilaurate, dibutyltin diacetate, dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin oxide, and dibutyltin dichloride; organonickel compounds such as nickel octylate and nickel naphthenate; organocobalt compounds such as cobalt octylate and cobalt naphthenate; organobismuth compounds such as bismuth octylate, bismuth neodecanoate, and bismuth naphthenate; titanium compounds such as tetraisopropyloxytitanate, dibutyltitanium dichloride, tetrabutyltitanium, butoxytitanium trichloride, aliphatic diketones, aromatic diketones, and titanium chelate complexes having at least one of alcohols having 2 to 10 carbon atoms as a ligand.
[0060] Examples of the amine catalyst include triethylenediamine, 2-methyltriethylenediamine, quinuclidine, 2-methylquinuclidine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetramethylpropylenediamine, N,N,N',N",N"-pentamethyldiethylenetriamine, N,N,N',N",N"-pentamethyl-(3-aminopropyl)ethylenediamine, N,N,N',N",N"-pentamethyldipropylenetriamine, N,N,N',N'-tetramethylhexamethylenediamine, bis(2-dimethylaminoethyl)ether, dimethylethanolamine, dimethylisopropanolamine, dimethylaminoethoxyethanol, N,N-dimethyl-N'-(2-hydroxyethyl)ethylenediamine, N,N-dimethyl-N'-(2-hydroxyethyl)propanediamine, bis(dimethylaminopropyl)amine, bis(dimethylaminopropyl)isopropanediamine, and the like. lopanolamine, 3-quinuclidinol, N,N,N',N'-tetramethylguanidine, 1,3,5-tris(N,N-dimethylaminopropyl)hexahydro-S-triazine, 1,8-diazabicyclo[5.4.0]undecene-7, N-methyl-N'-(2-dimethylaminoethyl)piperazine, N,N'-dimethylpiperazine, dimethylcyclohexylamine, N-methylmorpholine, N-ethylmorpholine, 1-methylimidazole, 1 ,2-dimethylimidazole, 1-isobutyl-2-methylimidazole, 1-dimethylaminopropylimidazole, N,N-dimethylhexanolamine, N-methyl-N'-(2-hydroxyethyl)piperazine, 1-(2-hydroxyethyl)imidazole, 1-(2-hydroxypropyl)imidazole, 1-(2-hydroxyethyl)-2-methylimidazole, 1-(2-hydroxypropyl)-2-methylimidazole, and the like.
[0061] Examples of the aliphatic cyclic amide compound include δ-valerolactam, ε-caprolactam, ω-enantholactam, η-capryllactam, β-propiolactam, etc. Among these, ε-caprolactam is more effective in promoting hardening.
[0062] (Acid anhydride (D2)) Examples of the acid anhydride (D2) include cyclic aliphatic acid anhydrides, aromatic acid anhydrides, and unsaturated carboxylic acid anhydrides, and can be used alone or in combination of two or more. More specifically, for example, phthalic acid anhydride, trimellitic acid anhydride, pyromellitic acid anhydride, benzophenone tetracarboxylic acid anhydride, dodecenyl succinic acid anhydride, polyadipic acid anhydride, polyazelaic acid anhydride, polysebacic acid anhydride, poly(ethyl octadecanedioic acid) anhydride, poly(phenyl hexadecanedioic acid) anhydride, tetrahydrophthalic acid anhydride, methyl tetrahydrophthalic acid anhydride, methyl hexahydrophthalic acid anhydride, hexahydrophthalic acid anhydride, methyl hymic acid anhydride, trialkyl tetrahydrophthalic acid anhydride, Examples of the anhydride include methylcyclohexene dicarboxylic anhydride, methylcyclohexene tetracarboxylic anhydride, ethylene glycol bistrimellitate dianhydride, HET anhydride, nadic anhydride, methylnadic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexane-1,2-dicarboxylic anhydride, 3,4-dicarboxy-1,2,3,4-tetrahydro-1-naphthalene succinic dianhydride, and 1-methyl-dicarboxy-1,2,3,4-tetrahydro-1-naphthalene succinic dianhydride.
[0063] In addition, the above-mentioned compounds may be modified with glycol as the acid anhydride (D2). Examples of glycols that can be used for modification include alkylene glycols such as ethylene glycol, propylene glycol, and neopentyl glycol; and polyether glycols such as polyethylene glycol, polypropylene glycol, and polytetramethylene ether glycol. Furthermore, copolymer polyether glycols of two or more of these glycols and / or polyether glycols may be used.
[0064] (Pigment (D3)) The pigment (D3) is not particularly limited, and examples thereof include organic pigments and inorganic pigments such as extender pigments, white pigments, black pigments, gray pigments, red pigments, brown pigments, green pigments, blue pigments, metal powder pigments, luminescent pigments, and pearlescent pigments, as well as plastic pigments, which are listed in the Paint Raw Materials Handbook 1970 Edition (compiled by the Japan Paint Manufacturers Association).
[0065] Examples of extender pigments include precipitated barium sulfate, powdered gourd, precipitated calcium carbonate, calcium bicarbonate, kansui stone, alumina white, silica, hydrous fine silica (white carbon), ultrafine anhydrous silica (aerosil), silica sand, talc, precipitated magnesium carbonate, bentonite, clay, kaolin, and yellow earth.
[0066] Specific examples of organic pigments include various insoluble azo pigments such as Benzidine Yellow, Hansa Yellow, Lake 4R, etc.; soluble azo pigments such as Lake C, Carmine 6B, Bordeaux 10, etc.; various (copper) phthalocyanine pigments such as Phthalocyanine Blue, Phthalocyanine Green, etc.; various chlorine dyeing lakes such as Rhodamine Lake, Methyl Violet Lake, etc.; various mordant dye pigments such as Quinoline Lake, Fast Sky Blue, etc.; various vat dye pigments such as Anthraquinone pigments, Thioindigo pigments, Perinone pigments, etc.; various quinacridone pigments such as Synchasia Red B, etc.; various dioxazine pigments such as Dioxazine Violet, etc.; various condensed azo pigments such as Chromophtal, etc.; aniline black, etc.
[0067] Examples of inorganic pigments include various chromates such as yellow lead, zinc chromate, and molybdate orange; various ferrocyanide compounds such as Prussian blue; various metal oxides such as titanium oxide, zinc oxide, mapico yellow, iron oxide, red iron oxide, chrome oxide green, and zirconium oxide; various sulfides or selenides such as cadmium yellow, cadmium red, and mercury sulfide; various sulfates such as barium sulfate and lead sulfate; various silicates such as calcium silicate and ultramarine; various carbonates such as calcium carbonate and magnesium carbonate; various phosphates such as cobalt violet and manganese purple; various metal powder pigments such as aluminum powder, gold powder, silver powder, copper powder, bronze powder, and brass powder; flake pigments of these metals, mica flake pigments; metallic pigments and pearl pigments such as mica flake pigments coated with metal oxides and micaceous iron oxide pigments; graphite, carbon black, and the like.
[0068] Examples of plastic pigments include "Grandol PP-1000" and "PP-2000S" manufactured by DIC Corporation.
[0069] The pigment (D3) to be used may be appropriately selected depending on the purpose. For example, it is preferable to use inorganic oxides such as titanium oxide and zinc oxide as white pigments, because they have excellent durability, weather resistance, and design properties, and it is preferable to use carbon black as a black pigment.
[0070] The amount of the pigment (D3) is, for example, 1 to 400 parts by mass per 100 parts by mass of the total solid content of the polyol composition (X) and the polyisocyanate composition (Y), and more preferably 10 to 300 parts by mass to improve adhesion and blocking resistance.
[0071] (Plasticizer (D4)) Examples of the plasticizer include phthalic acid plasticizers, fatty acid plasticizers, aromatic polycarboxylic acid plasticizers, phosphoric acid plasticizers, polyol plasticizers, epoxy plasticizers, polyester plasticizers, and carbonate plasticizers.
[0072] Examples of the phthalic acid plasticizer include phthalic acid ester plasticizers such as dimethyl phthalate, diethyl phthalate, dibutyl phthalate, diisobutyl phthalate, dihexyl phthalate, diheptyl phthalate, di-(2-ethylhexyl) phthalate, di-n-octyl phthalate, dinonyl phthalate, diisononyl phthalate, didecyl phthalate, diisodecyl phthalate, ditridecyl phthalate, diundecyl phthalate, dilauryl phthalate, distearyl phthalate, diphenyl phthalate, dibenzyl phthalate, butyl benzyl phthalate, dicyclohexyl phthalate, octyl decyl phthalate, dimethyl isophthalate, di-(2-ethylhexyl) isophthalate, and diisooctyl isophthalate; and tetrahydrophthalic acid ester plasticizers such as di-(2-ethylhexyl) tetrahydrophthalate, di-n-octyl tetrahydrophthalate, and diisodecyl tetrahydrophthalate.
[0073] Examples of fatty acid plasticizers include adipic acid plasticizers such as di-n-butyl adipate, di-(2-ethylhexyl) adipate, diisodecyl adipate, diisononyl adipate, di(C6-C10 alkyl) adipate, and dibutyl diglycol adipate; azelaic acid plasticizers such as di-n-hexyl azelate, di-(2-ethylhexyl) azelate, and diisooctyl azelate; and di-n-butyl sebacate, di-(2 Sebacic acid plasticizers such as di-n-ethylhexyl) sebacate and diisononyl sebacate; maleic acid plasticizers such as dimethyl maleate, diethyl maleate, di-n-butyl maleate and di-(2-ethylhexyl) maleate; fumaric acid plasticizers such as di-n-butyl fumarate and di-(2-ethylhexyl) fumarate; monomethyl itaconate, monobutyl itaconate, dimethyl itaconate, diethyl itaconate, dibutyl itaconate, Examples of the plasticizer include itaconic acid-based plasticizers such as luitaconate and di-(2-ethylhexyl) itaconate; stearic acid-based plasticizers such as n-butyl stearate, glycerol monostearate, and diethylene glycol distearate; oleic acid-based plasticizers such as butyl oleate, glyceryl monooleate, and diethylene glycol monooleate; citric acid-based plasticizers such as triethyl citrate, tri-n-butyl citrate, acetyl triethyl citrate, acetyl tributyl citrate, and acetyl tri-(2-ethylhexyl) citrate; ricinoleic acid-based plasticizers such as methyl acetyl ricinoleate, butyl acetyl ricinoleate, glyceryl monoricinoleate, and diethylene glycol monoricinoleate; and other fatty acid-based plasticizers such as diethylene glycol monolaurate, diethylene glycol dipelargonate, and pentaerythritol fatty acid esters.
[0074] Examples of aromatic polycarboxylic acid plasticizers include trimellitic acid plasticizers such as tri-n-hexyl trimellitate, tri-(2-ethylhexyl) trimellitate, tri-n-octyl trimellitate, triisooctyl trimellitate, triisononyl trimellitate, tridecyl trimellitate, and triisodecyl trimellitate; and pyromellitic acid plasticizers such as tetra-(2-ethylhexyl) pyromellitate and tetra-n-octyl pyromellitate.
[0075] Examples of the phosphoric acid plasticizer include triethyl phosphate, tributyl phosphate, tri-(2-ethylhexyl) phosphate, tributoxyethyl phosphate, triphenyl phosphate, octyl diphenyl phosphate, cresyl diphenyl phosphate, cresyl phenyl phosphate, tricresyl phosphate, trixylenyl phosphate, tris(chloroethyl) phosphate, tris(chloropropyl) phosphate, tris(dichloropropyl) phosphate, and tris(isopropylphenyl) phosphate.
[0076] Examples of polyol-based plasticizers include glycol-based plasticizers such as diethylene glycol dibenzoate, dipropylene glycol dibenzoate, triethylene glycol dibenzoate, triethylene glycol di-(2-ethylbutyrate), triethylene glycol di-(2-ethylhexoate), and dibutylmethylene bisthioglycolate; and glycerin-based plasticizers such as glycerol monoacetate, glycerol triacetate, and glycerol tributyrate.
[0077] Examples of epoxy plasticizers include epoxidized soybean oil, epoxy butyl stearate, di-2-ethylhexyl epoxy hexahydrophthalate, diisodecyl epoxy hexahydrophthalate, epoxy triglyceride, epoxidized octyl oleate, and epoxidized decyl oleate.
[0078] Examples of polyester plasticizers include adipic acid polyesters, sebacic acid polyesters, and phthalic acid polyesters.
[0079] Examples of carbonate plasticizers include propylene carbonate and ethylene carbonate.
[0080] Other examples of the plasticizer include partially hydrogenated terphenyls, adhesive plasticizers, and polymerizable plasticizers such as diallyl phthalate, acrylic monomers and oligomers, etc. These plasticizers can be used alone or in combination of two or more kinds.
[0081] (Phosphate Compound (D5)) Examples of the phosphoric acid compound (D5) include phosphoric acid, pyrophosphoric acid, triphosphoric acid, methyl acid phosphate, ethyl acid phosphate, butyl acid phosphate, dibutyl phosphate, 2-ethylhexyl acid phosphate, bis(2-ethylhexyl) phosphate, isododecyl acid phosphate, butoxyethyl acid phosphate, oleyl acid phosphate, tetracosyl acid phosphate, 2-hydroxyethyl methacrylate acid phosphate, and polyoxyethylene alkyl ether phosphate.
[0082] On the other hand, since the adhesive of the present invention has excellent boiling resistance, it is preferable not to add a silane coupling agent separately, which can reduce the risk of residual alcohol, especially residual methanol, remaining in the cured coating film of the adhesive.
[0083] (Adhesive Form) The adhesive of the present invention may be in the form of either a solvent-based or solventless type. In this specification, the term "solvent-based" adhesive refers to a form used in a method in which the adhesive is applied to a substrate, heated in an oven or the like to volatilize the organic solvent in the coating film, and then laminated to another substrate, that is, a so-called dry lamination method. Either or both of the polyol composition (X) and the polyisocyanate composition (Y) contain an organic solvent capable of dissolving (diluting) the constituent components of the polyol composition (X) and the polyisocyanate composition (Y) used in the present invention.
[0084] Examples of such organic solvents include esters such as methyl acetate, ethyl acetate, propyl acetate, butyl acetate, cellosolve acetate, etc., ketones such as acetone, methyl ethyl ketone, isobutyl ketone, cyclohexanone, etc., ethers such as tetrahydrofuran, dioxane, etc., aromatic hydrocarbons such as toluene, xylene, etc., halogenated hydrocarbons such as methylene chloride, ethylene chloride, etc., dimethyl sulfoxide, dimethyl sulfamide, etc. The organic solvent used as a reaction medium during the production of the components of the polyisocyanate composition (X) and the polyol composition (Y) may also be used as a diluent during coating.
[0085] In this specification, the term "solvent-free" adhesive refers to a form of adhesive used in a method in which the polyol composition (X) and the polyisocyanate composition (Y) are substantially free of the above-mentioned organic solvents, particularly ethyl acetate or methyl ethyl ketone, and the adhesive is applied to a substrate and then laminated to another substrate without a process of volatilizing the solvent by heating in an oven or the like, that is, a so-called non-solvent lamination method. When the organic solvent used as a reaction medium in the manufacture of the components of the polyol composition (X) and the polyisocyanate composition (Y) or the raw materials thereof cannot be completely removed and a trace amount of organic solvent remains in the polyol composition (X) and the polyisocyanate composition (Y), it is understood that the polyol composition (X) is substantially free of organic solvent. In addition, when the polyol composition (X) contains a low molecular weight alcohol, the low molecular weight alcohol reacts with the polyisocyanate composition (Y) to become a part of the coating film, so there is no need to volatilize it after application. Therefore, such a form is also treated as a solvent-free adhesive, and the low molecular weight alcohol is not considered to be an organic solvent.
[0086] The adhesive of the present invention is preferably used by mixing the polyisocyanate composition (Y) so that the ratio [NCO] / [OH] of the number of moles of isocyanate groups [NCO] contained in the polyol composition (X) to the number of moles of hydroxyl groups [OH] is 0.5 to 6.0.
[0087] <Laminate> The laminate of the present invention is obtained by laminating a plurality of substrates (films or papers) using the adhesive of the present invention by a dry lamination method or a non-solvent lamination method. There is no particular limitation on the film used, and a film can be appropriately selected according to the application. For example, for food packaging, polyolefin films such as polyethylene terephthalate (PET) film, polystyrene film, polyamide film, polyacrylonitrile film, polyethylene film (LLDPE: low density polyethylene film, HDPE: high density polyethylene film, MDOPE: uniaxially oriented polyethylene film, OPE: biaxially oriented polyethylene film) and polypropylene film (CPP: non-oriented polypropylene film, OPP: biaxially oriented polypropylene film), polyvinyl alcohol film, ethylene-vinyl alcohol copolymer film, etc. can be mentioned.
[0088] It is also preferable to use a biomass film formed from a material containing a biomass-derived component. Biomass films are sold by various companies, and for example, sheets such as those listed in the list of biomass certified products listed in the Japan Organics Resources Association can be used.
[0089] Specifically, well-known biomass films include those using ethylene glycol derived from biomass as a raw material. Biomass-derived ethylene glycol is made from ethanol (biomass ethanol) produced from biomass as a raw material. For example, biomass-derived ethylene glycol can be obtained by a method of producing ethylene glycol from biomass ethanol via ethylene oxide using a conventionally known method. In addition, commercially available biomass ethylene glycol may be used, and for example, biomass ethylene glycol commercially available from India Glycoal Limited can be suitably used.
[0090] For example, as an alternative to conventional polyethylene terephthalate films using petroleum-based raw materials, films containing biomass polyesters and biomass polyethylene terephthalate, which have biomass-derived ethylene glycol as the diol unit and fossil fuel-derived dicarboxylic acids as the dicarboxylic acid units, are known.
[0091] The dicarboxylic acid unit of the biomass polyester uses a dicarboxylic acid derived from a fossil fuel. As the dicarboxylic acid, an aromatic dicarboxylic acid, an aliphatic dicarboxylic acid, and a derivative thereof can be used without limitation. In addition to the above diol component and dicarboxylic acid component, the copolymer polyester may be a copolymer polyester containing a copolymer component as a third component, such as a bifunctional oxycarboxylic acid or at least one polyfunctional compound selected from the group consisting of a trifunctional or higher functional polyhydric alcohol, a trifunctional or higher functional polycarboxylic acid and / or its anhydride, and a trifunctional or higher functional oxycarboxylic acid, in order to form a crosslinked structure.
[0092] In addition, for example, as an alternative to conventional polyolefin films using petroleum-based raw materials, biomass polyolefin films such as biomass polyethylene films and biomass polyethylene-polypropylene films, which contain polyethylene resins made from biomass-derived ethylene glycol, are also known. The polyethylene resin is not particularly limited except that ethylene glycol derived from biomass is used as part of the raw material. Examples of the polyethylene resin include ethylene homopolymers and copolymers of ethylene and α-olefins with ethylene as the main component (ethylene-α-olefin copolymers containing 90% by mass or more of ethylene units). These may be used alone or in combination of two or more.
[0093] The α-olefin constituting the copolymer of ethylene and α-olefin is not particularly limited, and examples thereof include α-olefins having 4 to 8 carbon atoms, such as 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene. Known polyethylene resins, such as low-density polyethylene resin, medium-density polyethylene resin, and linear low-density polyethylene resin, can be used. Among them, linear low-density polyethylene resin (LLDPE) (a copolymer of ethylene and 1-hexene, or a copolymer of ethylene and 1-octene) is preferred from the viewpoint of making damage such as holes and tears even less likely to occur even when films are rubbed against each other, and has a density of 0.910 to 0.925 g / cm. 3 More preferred is a linear low density polyethylene resin in which
[0094] Biomass films made from biomass raw materials classified by the biomass plastic degree specified by ISO16620 or ASTM D6866 are also on the market. Radioactive carbon-14C exists in the atmosphere at a ratio of 1 in 1012 particles, and this ratio does not change with atmospheric carbon dioxide, so this ratio does not change even in plants that fix this carbon dioxide through photosynthesis. For this reason, the carbon in plant-derived resins contains radioactive carbon-14C. In contrast, the carbon in fossil fuel-derived resins contains almost no radioactive carbon-14C. Therefore, by measuring the concentration of radioactive carbon-14C in the resin with an accelerator mass spectrometer, the proportion of plant-derived resin in the resin, i.e., the biomass plastic degree, can be determined.
[0095] Examples of plant-derived low-density polyethylene, which is a biomass plastic having a biomass plastic content of 80% or more, preferably 90% or more as specified by ISO16620 or ASTM D6866, include Braskem products under the trade names "SBC818", "SPB608", "SBF0323HC", "STN7006", "SEB853", and "SPB681", and films using these as raw materials can be preferably used.
[0096] In addition, films and sheets containing starch, a biomass raw material, or polylactic acid are also known. These can be selected and used appropriately depending on the application.
[0097] The biomass film may be a laminate of multiple biomass films, or a laminate of a conventional petroleum-based film and a biomass film. These biomass films may be unstretched or stretched films, and the manufacturing method thereof is not limited.
[0098] The film may be one that has been subjected to a stretching treatment. As a stretching method, a typical method is to melt-extrude a resin into a sheet shape by an extrusion film forming method or the like, and then perform simultaneous biaxial stretching or sequential biaxial stretching. In the case of sequential biaxial stretching, it is common to first perform longitudinal stretching and then transverse stretching. Specifically, a method is often used in which longitudinal stretching utilizing the speed difference between rolls and transverse stretching using a tenter are combined.
[0099] The film surface may be subjected to various surface treatments such as flame treatment and corona discharge treatment as necessary so that an adhesive layer free from defects such as film breakage and repellency is formed.
[0100] Alternatively, a film having a vapor-deposited layer of a metal such as aluminum or a metal oxide such as silica or alumina, or a barrier film containing a gas barrier layer of polyvinyl alcohol, ethylene-vinyl alcohol copolymer, vinylidene chloride, etc. can be used. By using such a film, a laminate having a barrier property against water vapor, oxygen, alcohol, inert gas, volatile organic compounds (fragrances), etc. can be obtained.
[0101] The paper can be made of any known paper base material without any particular limitation. Specifically, the paper is made by a known paper machine using natural fibers for papermaking such as wood pulp, but the papermaking conditions are not particularly specified. Examples of natural fibers for papermaking include wood pulp such as softwood pulp and hardwood pulp, non-wood pulp such as Manila hemp pulp, sisal hemp pulp, and flax pulp, and pulp obtained by chemically modifying these pulps. As the type of pulp, chemical pulp, ground pulp, chemi-ground pulp, thermomechanical pulp, etc., made by sulfate cooking method, acidic / neutral / alkaline sulfite cooking method, soda salt cooking method, etc., can be used. In addition, various commercially available wood-free papers, coated papers, backing papers, impregnated papers, cardboard, paperboard, etc. can also be used.
[0102] The laminate obtained by using the adhesive of the present invention has excellent resistance to boiling treatment. Therefore, it can be used not only for general applications but also for applications requiring boiling treatment. Specific configurations include, but are not limited to, transparent vapor-deposited Ny film / adhesive layer / sealant film, transparent vapor-deposited PET film / adhesive layer / sealant film, transparent vapor-deposited PET film / adhesive layer / Ny film / adhesive layer / sealant film, OPP film / adhesive layer / transparent vapor-deposited PET film / adhesive layer / sealant film, Ny film / adhesive layer / transparent vapor-deposited PET film / adhesive layer / sealant film, PET film / adhesive layer / transparent vapor-deposited PET film / adhesive layer / sealant film, transparent vapor-deposited Ny film / adhesive layer / transparent vapor-deposited PET film / adhesive layer / sealant film, transparent vapor-deposited PET film / adhesive layer / transparent vapor-deposited PET film / adhesive layer / sealant film, and transparent vapor-deposited PET film / adhesive layer / transparent vapor-deposited PET film / adhesive layer / sealant film. In addition, an aluminum vapor-deposited film may be used instead of the transparent vapor-deposited film.
[0103] In the case where a plurality of adhesive layers are present in these laminates, it is preferable that the adhesive of the present invention is used for the adhesive layer in contact with the transparent vapor deposition layer or aluminum vapor deposition layer. Delamination is particularly likely to occur between the transparent vapor deposition layer or aluminum vapor deposition layer and the adhesive layer when a boiling treatment is performed, but such a defect can be suppressed by using the adhesive of the present invention. The other adhesive may be bonded using the adhesive of the present invention, or may be bonded using a general-purpose urethane adhesive if there is no particular problem. Generally, a printed layer, which will be described later, is provided at an appropriate position in a laminate for packaging material, but the description is omitted in the above example.
[0104] The laminate of the present invention may have a printed layer between the adhesive layer and the substrate (usually the substrate that is the outermost layer with respect to the contents). The printed layer is formed by a general printing method that has been used for printing on films using various printing inks such as gravure ink, flexo ink, offset ink, stencil ink, and inkjet ink.
[0105] When the adhesive is a solvent-based adhesive, the adhesive of the present invention is applied to one substrate using a roll such as a gravure roll, and the organic solvent is evaporated by heating in an oven or the like, and then the other substrate is laminated to obtain the laminate of the present invention. After lamination, it is preferable to carry out an aging treatment. The aging temperature is preferably room temperature to 80°C, and the aging time is preferably 12 to 240 hours.
[0106] When the adhesive is a solventless type, the adhesive of the present invention, which has been preheated to about 40°C to 100°C, is applied to one of the substrates using a roll such as a coat roll, and the other substrate is immediately laminated to obtain the laminate of the present invention. After lamination, it is preferable to carry out an aging treatment. The aging temperature is preferably room temperature to 70°C, and the aging time is preferably 6 to 240 hours.
[0107] The amount of adhesive applied is adjusted as appropriate. For example, in the case of a solvent-based adhesive, the solid content is 1 g / m 2 More than 10g / m 2 Less than 2 g / m 2 More than 5g / m 2Adjust the amount of adhesive applied so that it is as follows: For a solvent-free adhesive, the amount of adhesive applied is, for example, 1 g / m 2 More than 5g / m 2 Less than 1 g / m 2 More than 3.5g / m 2 The following is the result.
[0108] The laminate of the present invention is a laminate of two substrates bonded together with the adhesive of the present invention, but may contain other substrates as necessary. The method for laminating the other substrates may be a known method, such as a dry lamination method, a non-solvent lamination method, a thermal lamination method, a heat seal method, or an extrusion lamination method. The adhesive used in this case may or may not be the adhesive of the present invention. The other substrates may be the same as the substrates described above.
[0109] <Packaging material> The packaging material of the present invention is obtained by forming the above-mentioned laminate into a bag shape and heat sealing it to obtain the form of the packaging material. The packaging material may be in the form of a three-side sealed bag, a four-side sealed bag, a gusseted packaging bag, a pillow packaging bag, a Goebel Top type bottomed container, a Tetra Classic, a Brueck type, a tube container, a paper cup, a lid, etc. The packaging material of the present invention may also be appropriately provided with an easy-opening treatment or a resealable means.
[0110] The packaging material of the present invention can be used industrially mainly as a packaging material for filling food, detergent, and medicine. Specific applications include liquid laundry detergent, liquid kitchen detergent, liquid bath detergent, liquid bath soap, liquid shampoo, liquid conditioner, and pharmaceutical tablets as detergents and medicines. It can also be used as a secondary packaging material for packaging the above-mentioned containers. EXAMPLES
[0111] The present invention will be described in more detail below with reference to specific synthesis examples and examples, but the present invention is not limited to these examples. In the following examples, "parts" and "%" respectively represent "parts by mass" and "% by mass" unless otherwise specified.
[0112] <Polyol composition (X)> (Reaction Product (A-1)) In a reaction vessel equipped with a stirrer, a thermometer, a nitrogen gas inlet tube, a rectification tube, a water separator, etc., 7.2 parts of ethylene glycol, 15.8 parts of diethylene glycol, 22.5 parts of neopentyl glycol, 21.9 parts of adipic acid, 4.6 parts of sebacic acid, 28.0 parts of isophthalic acid, and 1.3 parts of KBM-403 (Shin-Etsu Silicone, 3-glycidoxypropyltrimethoxysilane) were charged under nitrogen gas introduction. The temperature was gradually raised under normal pressure nitrogen gas flow to 250°C while performing a dehydration reaction, and the reaction was carried out at 250°C for 2 hours. When it was confirmed that the contents were transparent and the top temperature of the rectification tower was 80°C or less, the temperature was lowered to 240°C, the rectification tower was switched to a condenser, the line was connected to a vacuum pump, and the reaction was continued under a reduced pressure of 30 to 60 Torr until a predetermined acid value and viscosity were reached, and a reaction product (A-1) was obtained. The reaction product (A-1) had an acid value of 0.7 mg KOH / g and a hydroxyl value of 159.0 mg KOH / g.
[0113] (Reaction Product (A-2)) In a reaction vessel equipped with a stirrer, a thermometer, a nitrogen gas inlet tube, a rectification tube, a water separator, etc., 7.2 parts of ethylene glycol, 15.8 parts of diethylene glycol, and 22.5 parts of neopentyl glycol were charged under nitrogen gas introduction, and the mixture was heated and dissolved while stirring. Then, 21.9 parts of adipic acid, 4.6 parts of sebacic acid, 28.0 parts of isophthalic acid, and 6.8 parts of KBM-403 were charged at 120-130°C. The temperature was gradually increased under a pressure of about 0.5 MPa to 240°C while performing a dehydration reaction, and the pressure was released after reaching 240°C. When it was confirmed that the contents were transparent and the top temperature of the rectification tower was 80°C or less, the rectification tower was switched to a condenser, a line was connected to a vacuum pump, and the reaction was continued under a reduced pressure of 30-60 Torr until the specified acid value and viscosity were reached, to obtain a reaction product (A-2). The reaction product (A-2) had an acid value of 0.6 mg KOH / g and a hydroxyl value of 154.0 mg KOH / g.
[0114] (Reaction Product (A-3)) In a reaction vessel equipped with a stirrer, a thermometer, a nitrogen gas inlet tube, a rectification tube, a water separator, etc., 7.2 parts of ethylene glycol, 15.8 parts of diethylene glycol, and 22.5 parts of neopentyl glycol were charged under nitrogen gas introduction, and the mixture was heated and dissolved while stirring. Then, 21.9 parts of adipic acid, 4.6 parts of sebacic acid, 28.0 parts of isophthalic acid, and 3.2 parts of KBE-903 (Shin-Etsu Silicone, 3-aminopropyltriethoxysilane) were charged at 120-130°C. The temperature was gradually increased under normal pressure nitrogen gas flow while performing a dehydration reaction, and the reaction was performed at 250°C for 2 hours. When it was confirmed that the contents were transparent and the top temperature of the rectification tower was 80°C or less, the temperature was lowered to 230°C, xylene was added, and the dehydration reaction was promoted while refluxing xylene at the same temperature using a water separator. When the acid value fell below 5.0 mgKOH / g, the distillation column was switched to a condenser, and a line was connected to a vacuum pump to remove xylene under reduced pressure of 30 to 60 Torr. The reaction was continued until the specified acid value and viscosity were reached, and the reaction product (A-3) was obtained. The reaction product (A-3) had an acid value of 0.8 mg KOH / g and a hydroxyl value of 156.0 mg KOH / g.
[0115] (Reaction Product (A-4)) In a reaction vessel equipped with a stirrer, a thermometer, a nitrogen gas inlet tube, a rectification tube, a water separator, etc., 14.0 parts of ethylene glycol and 20.9 parts of neopentyl glycol were charged under nitrogen gas introduction, and the mixture was heated and dissolved while stirring. Then, 24.3 parts of adipic acid, 20.4 parts of isophthalic acid, 20.4 parts of terephthalic acid, and 1.0 parts of KBM-403 were charged at 120-130°C. The mixture was gradually heated under a pressure of about 0.5 MPa to 260°C while carrying out a dehydration reaction, and the pressure was released after reaching 260°C. When it was confirmed that the contents were transparent and the top temperature of the rectification tower was 80°C or less, the temperature was lowered to 230°C, xylene was added, and the dehydration reaction was promoted while refluxing xylene at the same temperature using a water separator. When the acid value fell below 5.0 mgKOH / g, the distillation column was switched to a condenser, and a line was connected to a vacuum pump to remove xylene under a reduced pressure of 30 to 60 Torr. The reaction was continued until the specified acid value and viscosity were reached, yielding the reaction product (A-4'). The reaction product (A-4') had an acid value of 1.2 mg KOH / g and a hydroxyl value of 27.0 mg KOH / g.
[0116] In a reaction vessel equipped with an agitator, a temperature sensor, a nitrogen gas inlet tube, and a cooling tube, 97.0 parts of the reaction product (A-4'), 53.8 parts of ethyl acetate, and 0.02 parts of dibutyltin dilaurate as a polymerization catalyst were charged. After heating to 60°C under normal pressure nitrogen gas flow, 3.0 parts of isophorone diisocyanate were charged and heated to 80°C, and a urethane reaction was carried out at 80°C. After confirming that the specified viscosity was reached and the residual isocyanate content was 0.05% or less, the temperature was lowered to 50°C and the non-volatile content was adjusted with ethyl acetate to obtain the reaction product (A-4). The reaction product (A-4) had an acid value calculated on a solid basis of 1.1 mgKOH / g, a hydroxyl value calculated on a solid basis of 11.9 mgKOH / g, and a non-volatile content of 65.0%.
[0117] (Reaction Product (A-5)) In a reaction vessel equipped with a stirrer, a thermometer, a nitrogen gas inlet tube, a rectification tube, a water separator, etc., 14.0 parts of ethylene glycol and 20.9 parts of neopentyl glycol were charged under nitrogen gas introduction, and the mixture was heated and dissolved while stirring. Then, 24.3 parts of adipic acid, 20.4 parts of isophthalic acid, 20.4 parts of terephthalic acid, and 1.0 parts of KBM-403 were charged at 120-130°C. The temperature was gradually increased under a pressure of about 0.5 MPa to 260°C while performing a dehydration reaction, and the pressure was released after reaching 260°C. When it was confirmed that the contents were transparent and the top temperature of the rectification tower was 80°C or less, the temperature was lowered to 240°C, the rectification tower was switched to a condenser, the line was connected to a vacuum pump, and the reaction was continued under a reduced pressure of 30-60 Torr until the specified acid value and viscosity were reached, to obtain a reaction product (A-5'). The reaction product (A-5') had an acid value of 0.8 mg KOH / g and a hydroxyl value of 26.2 mg KOH / g.
[0118] In a reaction vessel equipped with an agitator, a temperature sensor, a nitrogen gas inlet tube, and a cooling tube, 97.0 parts of the reaction product (A-5'), 53.8 parts of ethyl acetate, and 0.02 parts of dibutyltin dilaurate as a polymerization catalyst were charged. After heating to 60°C under normal pressure nitrogen gas flow, 3.0 parts of isophorone diisocyanate were charged and heated to 80°C, and a urethane reaction was carried out at 80°C. After confirming that the specified viscosity was reached and the residual isocyanate content was 0.05% or less, the temperature was lowered to 50°C and the non-volatile content was adjusted with ethyl acetate to obtain the reaction product (A-5). The reaction product (A-5) had an acid value of 0.8 mg KOH / g in terms of solid, a hydroxyl value of 11.0 mg KOH / g in terms of solid, and a non-volatile content of 65.0%.
[0119] (Reaction Product (AH-1)) In a reaction vessel equipped with a stirrer, a thermometer, a nitrogen gas inlet tube, a rectification tube, a water separator, etc., 7.2 parts of ethylene glycol, 15.8 parts of diethylene glycol, 22.5 parts of neopentyl glycol, 21.9 parts of adipic acid, 4.6 parts of sebacic acid, and 28.0 parts of isophthalic acid were charged under nitrogen gas introduction. The temperature was gradually raised under normal pressure nitrogen gas flow while performing a dehydration reaction, and the reaction was carried out at 250°C for 2 hours. When it was confirmed that the contents were transparent and the top temperature of the rectification tower was 80°C or less, the temperature was lowered to 240°C, the rectification tower was switched to a condenser, the line was connected to a vacuum pump, and the reaction was continued under a reduced pressure of 30 to 60 Torr until the predetermined acid value and viscosity were reached, and a reaction product (AH-1) was obtained. The reaction product (AH-1) had an acid value of 1.3 mg KOH / g and a hydroxyl value of 168.0 mg KOH / g.
[0120] (Reaction Product (AH-2)) In a reaction vessel equipped with a stirrer, a thermometer, a nitrogen gas inlet tube, a rectification tube, a water separator, etc., 14.0 parts of ethylene glycol and 20.9 parts of neopentyl glycol were charged under nitrogen gas introduction, and the mixture was heated and dissolved while stirring. Then, 24.3 parts of adipic acid, 20.4 parts of isophthalic acid, and 20.4 parts of terephthalic acid were charged at 120-130°C. The mixture was gradually heated under a pressure of about 0.5 MPa to 260°C while carrying out a dehydration reaction, and the pressure was released after reaching 260°C. When it was confirmed that the contents were transparent and the top temperature of the rectification tower was 80°C or less, the temperature was lowered to 230°C, xylene was added, and the dehydration reaction was promoted while refluxing xylene at the same temperature using a water separator. When the acid value fell below 5.0 mgKOH / g, the distillation column was switched to a condenser, and a line was connected to a vacuum pump to remove xylene under a reduced pressure of 30-60 Torr. The reaction was continued until the specified acid value and viscosity were reached, yielding the reaction product (AH-2'). The reaction product (AH-2') had an acid value of 1.3 mg KOH / g and a hydroxyl value of 27.0 mg KOH / g.
[0121] In a reaction vessel equipped with an agitator, a temperature sensor, a nitrogen gas inlet tube, and a cooling tube, 97.0 parts of the reaction product (A-2'), 53.8 parts of ethyl acetate, and 0.02 parts of dibutyltin dilaurate as a polymerization catalyst were charged. After heating to 60°C under normal pressure nitrogen gas flow, 3.0 parts of isophorone diisocyanate were charged and heated to 80°C, and a urethane reaction was carried out at 80°C. After confirming that the specified viscosity was reached and the residual isocyanate content was 0.05% or less, the temperature was lowered to 50°C and the non-volatile content was adjusted with ethyl acetate to obtain the reaction product (AH-2). The reaction product (AH-2) had an acid value of 1.3 mg KOH / g on a solid basis, a hydroxyl value of 13.1 mg KOH / g on a solid basis, and a non-volatile content of 65.0%.
[0122] The obtained reaction products (A-1) to (A-5), (AH-1), (AH-2), KBM-403, and KBE-903 were mixed in the amounts (solid content) shown in Tables 1 and 2 to obtain polyol compositions (X) for the Examples and Comparative Examples.
[0123] <Polyisocyanate composition (Y)> (Polyisocyanate compound (C-1)) A polyisocyanate composition (C-1) was prepared by mixing a commercially available nurate form of isophorone diisocyanate and a nurate form of hexamethylene diisocyanate in a ratio of 1:4 parts by weight.
[0124] (Polyisocyanate compound (C-2)) A trifunctional polyisocyanate obtained by adding tolylene diisocyanate to trimethylolpropane (product name: DIC Dry KW-75 manufactured by DIC Corporation, solid content: 75%) was used as a polyisocyanate composition (C-2).
[0125] <Preparation of adhesive> The reactive adhesives for the Examples and Comparative Examples were prepared by mixing the reaction product (A), the polyisocyanate composition (C), and the silane coupling agent in the ratios shown in Tables 3 and 4. When a solvent was used, the viscosity was adjusted using ethyl acetate.
[0126] <Production of Laminate> The coating amount was 3.2 g / m2 on the deposition surface of a 12 μm-thick silica-deposited PET film (Techbarrier L, manufactured by Mitsubishi Chemical Corporation). 2 The adhesive was applied so that the thickness of the laminate was 100 μm, and then the adhesive-coated surface was bonded to a 60 μm-thick LLDPE film (linear low-density polyethylene film TUX(TM)HC, manufactured by Mitsui Chemicals Tocello Co., Ltd.) Aging was performed at 40° C. for 4 days to obtain a laminate for evaluation.
[0127] <Evaluation> (Residual alcohol content) The amount of residual alcohol contained in the solid content of the polyol composition (X) used in the examples and comparative examples was measured by carrying out 13C-NMR measurement under the following conditions. Methanol was added to the model resin in advance, and the amount was judged in the following two stages based on the detection limit of methanol measured in the same manner as for the polyol composition (X). ○: Less than 0.1 wt% (not detectable) ×: 0.1 wt% or more
[0128] (Investigation of the detection limit using a model resin (with MeOH added)) Adhesive model: 750 mg of the adhesive model mixed as described in (1) to (3) below was weighed out and dissolved in 250 μl of deuterated chloroform to prepare a measurement sample. (1) Silane coupling agent not added: MeOH=99.9:0.1wt% (2) Silane coupling agent not added: MeOH=99.7:0.3wt% (3) Silane coupling agent not added: MeOH=99.5:0.5wt% (sample) 750 mg of the sample was dissolved in 250 μl of deuterated chloroform to prepare a measurement sample. (NMR measurement conditions) Equipment: JEOL ECX-400P Measurement temperature: room temperature Resonance frequency: 100MHz Measurement nuclei / parameters: 13C-NMR (fully decoupled) / Scan 1000, Relaxation delay 2 s, Flip angle 30 deg, x_offset 100 ppm, x_sweep 250 ppm, x_points 32768.
[0129] (Adhesive strength) The laminate was cut into a length of 300 mm and a width of 15 mm to prepare a test piece. Using an Instron tensile tester, the laminate was pulled at a peel rate of 300 mm / min in an environment of 25°C, and the 180-type peel strength (N / 15 mm) between the silica-deposited PET film and the LLDPE film was measured at a width of 15 mm.
[0130] (Boiling resistance) The laminate for evaluation was cut to 150 mm x 300 mm, folded so that the LLDPE film was on the inside, and two sides were heat-sealed at 1 atm, 180 ° C, and 1 second to produce a pouch. The pouch was filled with 1 / 1 / 1 sauce (meat sauce: vegetable oil: vinegar = 1:1:1), and the remaining side was heat-sealed under the same conditions to seal the pouch. The pouch filled with the contents was immersed in hot water at 98 ° C and boiled for 1 hour for sterilization. The pouch after removing the contents was opened and cut into a strip with a width of 15 mm to prepare a test piece. Using an Instron tensile tester, the film was pulled at a peel speed of 300 mm / min in an environment of 25 ° C, and the 180 ° C peel strength (N / 15 mm) between the silica-deposited PET film / LLDPE film was measured at a width of 15 mm. Furthermore, if delamination occurred at the time of completion of the boiling sterilization treatment, it was marked as "Delamination" and the peel strength was not measured.
[0131] [Table 1]
[0132] [Table 2]
[0133] [Table 3]
[0134] [Table 4]
Claims
1. a polyol composition (X) containing a reaction product (A) obtained by esterification of a composition (A') containing a polyvalent carboxylic acid (a), a polyhydric alcohol (b), and a compound (c) having a functional group reactive with a carboxyl group or a hydroxyl group, and an alkoxysilyl group; A polyisocyanate composition (Y); A two-component curing adhesive comprising:
2. 2. The two-component curing adhesive according to claim 1, wherein the compound (c) is present in an amount of 0.5% by mass or more and 10% by mass or less in the composition (A').
3. The two-component curing adhesive according to claim 1 , wherein the polyol composition (X) contains a polyol (B).
4. The composition (A') contains a polyisocyanate (d), 2. The two-component curing adhesive according to claim 1, wherein the reaction product (A) is a reaction product of the polyvalent carboxylic acid (a), the polyhydric alcohol (b), the compound (c), and the polyisocyanate (d).
5. 2. The two-component curing adhesive according to claim 1, wherein the functional group reactive with a carboxyl group or a hydroxyl group is an amino group.
6. 2. The two-component curing adhesive according to claim 1, wherein the functional group reactive with a carboxyl group or a hydroxyl group is an epoxy group.
7. A laminate comprising a first substrate, a second substrate, and an adhesive layer disposed between the first substrate and the second substrate, the adhesive layer being a cured coating film of the two-component curing adhesive according to any one of claims 1 to 6.
8. A packaging material comprising the laminate according to claim 7.
Citation Information
Patent Citations
Steam-resistant solvent-free laminating adhesive and preparation method thereof
CN102604583A
Adhesive composition for plastic*metal foil composite packaging material
JP1979090239A
Laminated film and packaging bag excellent in boiling burst resistance using the same
JP1997295386A
Adhesive for dry laminate
JP2000154365A
Packaging material for retort
JP2000177771A